Kontribusi Mahasiswa KKN UNP Dalam Meningkatkan Kesehatan Mental Remaja di SMPN 6 Lubuk Basung - Ayanda, Felyn; Surya, Winanda; Takwin, Bintang Sani; Fatma, Eizah; Elvira, Mariza (Journal of Humanity Dedication, 2024)
Mental health in adolescents has a significant influence on adolescents' daily lives, which involves adolescents' thought patterns, feelings/moods, and actions. This article aims to examine the contribution made by UNP KKN students in improving the mental health of teenagers at SMPN 6 Lubuk Basung using a sample of 40 children from grades 1-3 of junior high school. This sample was taken using random sampling/probability sampling techniques. The contributions made by KKN students use presentation/lecture and group counseling methods. Data collected used observation and library research techniques. The data that has been obtained is analyzed using descriptive statistical techniques. This contribution activity has had a positive impact on improving the mental health of teenagers at SMPN 6 Lubuk Basung.